The Clinical Characteristics of Other HLA-B Types in Chinese Ankylosing Spondylitis Patients - Wu, Xinyu; Wu, Jialing; Li, Xiaomin; Wei, Qiujing; Lv, Qing; Zhang, Pingping; Zheng, Xuqi; Chen, Zena; Cao, Shuangyan; Tu, Liudan; Gu, Jieruo (Frontiers in Medicine, 2021)
HLA-B27 has an established relationship with the development of ankylosing spondylitis (AS). After reviewing the HLA-B genotype from 407 Chinese subjects (318 patients and 89 sex-matched controls), we found that 252 patients and 32 controls were HLA-B27(+) and that HLA-B*27:04 was the dominant HLA-B27 subtype (N = 224). In all participants, HLA*27:04 homozygous were only detected in two patients. In the HLA-B27(+) group, HLA-B40 was observed in 51 cases and one control (p < 0.05, OR = 7.87, 95% CI 1.05–59.0); of these, the most genotype was HLA-B*27:04/B*40:01(N = 38). Two hundred thirty-nine patients' clinical information was recorded. Cases with HLA-B27/B46 had more peripheral joint involvement (OR = 3.95, 95% CI 1.77–8.79) in HLA-B27(+) AS. HLA-B*15:02 may be a significant risk element to peripheral joint involvement (p < 0.05) in HLA-B27(−) patients. Therefore, we believe HLA-B*40:01, HLA-B*46:01, and HLA-B*15:02 can be the test indicators for AS diagnostic value.